High speed milling of silicon carbide with diamond coated end mills - Konneh, Mohamed; Iqbal, Mohammad; Kasim, Md Asnawi; Mohd Isa, Nurbahiah (Trans Tech Publications, 2012)
The primary applications of silicon carbide SiC-based materials, which include include micro-structures, optoelectronic devices, high temperature electronics, radiation hard electronics and high power/high frequency devices to name a few have necessitated the need for machining SiC. The paper presents the outcome of milling of silicon carbide using diamond coated end mill under different machining conditions in order to determine the surface roughness parameter after the machining processes. Relationship between the machining parameters and response variables has been established and a mathematical model has been predicted, the minimum roughness value, Rz being 0.19 μm.